Advances in citrus nutrition - Srivastava, Anoop Kumar (Springer Netherlands, 2012)
Citrus nutrition has been the subject of worldwide research to not only soil scientists, but to researchers covering various other disciplines as well. Despite many breakthroughs in diagnosis and management of nutrient constraints, citrus nutritionists are still baffled by the complex processes associated with precise field diagnosis of different nutrient constraints. Hence, currently available diagnostic tools are more applicable to next season's crop, instead of addressing the constraints in the current standing crop. In this regard, there has been some distinctive developments. For example, the application of geospatial tools including non-destructive proximal sensing, metalloenzymes through increasing involvement of genomics and metabolomics (e.g., expressed tag analysis), exploiting the dynamic relationship between soil enzymes and fertility variations, etc. Studying the partitioning of nutrients across critical growth stages has, not only improved our understanding on nutritional physiology, but enabled researchers to modulate nutrient requirement according to nutrient demand of growing leaves and fruits according to source-sink relationship. This is where nutrient use efficiency intervenes best to unravel many of the mysteries associated with nutrient requirement at various phenophases of crops. The major abiotic constraints in the form of calcium carbonate (induced iron chlorosis on alkaline soils and Al-toxicity; induced nutrient transformations on acid soils) have taken the understanding of citrus nutrition to another level of excellence, highlighting their significance in cutting down the efficiency of  nutrient use. These developments have undoubtedly added a new dimension to diagnosis of nutrient constraints. As many as 30 chapters from 72 eminent researchers spread over 19 countries have made this maiden book on Citrus Nutrition more special both in terms of quality as well as attracting a global readership.